Analysis of the structural reliability of communication networks supporting protective switching mechanisms for one protected section and one backup section - K. А. Batenkov; A. B. Fokin (Российский технологический журнал, 2024)
Objectives. The service level agreement is an important tool used in building reasonable relations between subscribers and operators of telecommunication networks. This includes the quality of services provided. One key component is reliability as assessed by the availability factor. The most suitable model for assessing the reliability of the service provided is a random graph model based on the service contour. This is the set of technical resources involved in the provision of this service. In this formulation, the assessment of the reliability of the service is based on the reliability of elements which constitute the telecommunications network (graph), nodes (vertices) and communication lines (edges). At the same time, the availability factors of nodes and lines are determined by the design features of the distribution environment, as well as the technical means used to organize them. The purpose of this work is to develop an approach to analyzing the reliability of telecommunication networks which support protective switching mechanisms for one protected and one backup sections.Methods. The following methods are used: theory of random graphs, matrices, probabilities and computer modeling.Results. The elements of the route, both basic and reserving, are divided into three groups. The first indicates permanent unchangeable parts of the paths, the second group identifies the reserved sections, and the third group indicates the reserving sections. At the same time, each of the reserved and reserving sections is formed on the basis of specified preferences. They are usually aimed at increasing the resulting reliability, although other rules may be used. In the case of protective switching schemes for one protected section and one backup sections, a variant of forming routes used for further calculations of the reliability indicator is shown.Conclusions. Using the example of a backbone network, the study shows that the use of protective switching mechanisms for the case of one required transmission route demonstrates a significant increase in reliability, with the exception of the use of protective switching in sections. This is primarily due to the topology features of the network under consideration.